Spotlight on risankizumab and its potential in the treatment of plaque psoriasis: evidence to date - Machado Á; Torres T (Dove Medical Press, 2018)
Álvaro Machado,1 Tiago Torres1,2 1Department of Dermatology, Centro Hospitalar Universitário do Porto, Porto, Portugal; 2Instituto de Ciências Biomédicas Abel Salazar, University of Porto, Porto, Portugal Abstract: Psoriasis is a common chronic immune-mediated skin disease, with systemic involvement and significant impact in patients’ quality of life. Several highly specific treatments have been developed over the years, such as tumor necrosis factor-α inhibitors, a nonselective IL-23 inhibitor (ustekinumab), and most recently IL-17 inhibitors. Risankizumab is a monoclonal antibody which targets IL-23p19 without binding IL-12. This novel therapeutic approach is expected to have advantages over the recently approved anti-IL-17 agents, such as the avoidance of Candida infections and neutropenia. In addition, unlike ustekinumab, the selective inhibition of IL-23 may preserve IL-12-dependent functions such as protection against infections and tumor immune surveillance. Risankizumab showed an excellent efficacy when compared to placebo and ustekinumab, with higher Psoriasis Area Severity Index (PASI) 75, PASI 90, and PASI 100 rates, along with a convenient every 12-week maintenance dosing regimen. Overall, risankizumab was well tolerated and the most common adverse event was upper respiratory tract infection. In the near future, further data will be available not only in psoriasis but also in Crohn’s disease and psoriatic arthritis fields. Head-to-head trials comparing risankizumab with other IL-23 inhibitors and with IL-17 inhibitors will be crucial to reveal the role of risankizumab in the treatment of psoriasis. Keywords: psoriasis, IL-23, risankizumab